Judicial Approach Towards Transgender Rights: An Analysis of the Nalsa Judgment and Beyond (Journal of Advances and Scholarly Researches in Allied Education, 2025)
With the historic National Legal Services Authority v. Union of India (NALSA) ruling in 2014, the Supreme Court upheld the constitutional rights of transgender people to self-identify their gender and live with dignity, marking a revolutionary change in the country's acceptance of transgender rights. The groundwork for comprehensive legal and social frameworks that address the marginalization and prejudice experienced by the transgender population was established by this ruling. Nevertheless, difficulties in implementing rights pertaining to social security, work, healthcare, and education continue despite progressive court rulings.  This paper critically analyses the judicial approach towards transgender rights, examining the evolution from the NALSA judgment to subsequent legal developments such as the Arun Kumar and Chinmayee Jena cases, alongside legislative measures like the Transgender Persons (Protection of Rights) Act, 2019. It explores how judicial activism continues to shape gender justice and inclusivity in contemporary India.